If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + -5(x + -1) + 3x = -1(2x + -15) Reorder the terms: 20 + -5(-1 + x) + 3x = -1(2x + -15) 20 + (-1 * -5 + x * -5) + 3x = -1(2x + -15) 20 + (5 + -5x) + 3x = -1(2x + -15) Combine like terms: 20 + 5 = 25 25 + -5x + 3x = -1(2x + -15) Combine like terms: -5x + 3x = -2x 25 + -2x = -1(2x + -15) Reorder the terms: 25 + -2x = -1(-15 + 2x) 25 + -2x = (-15 * -1 + 2x * -1) 25 + -2x = (15 + -2x) Add '2x' to each side of the equation. 25 + -2x + 2x = 15 + -2x + 2x Combine like terms: -2x + 2x = 0 25 + 0 = 15 + -2x + 2x 25 = 15 + -2x + 2x Combine like terms: -2x + 2x = 0 25 = 15 + 0 25 = 15 Solving 25 = 15 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -6/7-1/3 | | (d-7)2=1 | | 2/3t+1/t=5/9 | | x+2/5=6 | | (8x^2+10x^3)-(4x^2-6x^3)= | | (3/17)/(27/34)-(8/63)*(7/40) | | 0.08-0.02(x+1)=-0.04(3-x) | | 7y+4-y+8= | | 4m-1/2=5+m | | 5(v+5)=-3(3v-7)+2v | | 3x+1=11x-4 | | 2x+(2*3x+5)=945 | | 7(2n+4)=9(4n+5)+7 | | 4d^2-2d=0 | | 4/5x=32 | | -3x+4=4x-17 | | 6(x-2)/9=4(x+1)/12 | | 7(x+1)+7=2x+5(3+x) | | -9+12x+13k-5x-2k-25= | | 5x-3=-3x+1 | | -19=5t | | -9(x-10)=17-8x | | 3x+(2*3x+5)=945 | | 6x-(7x+6)=4x-26 | | y=3.2x+0.7 | | 1.50x+2.00=20 | | 14=-7u | | 6y+2(y-9)=6(y+1)-3 | | x-5x-60-x-13=-17 | | 7(2n+5)=8(6n+1)+6 | | k(2k+2)-6(2k+4)=k(2k-4)+(6k+9) | | -30/6= |